ANALISIS PENGARUH MODAL DAN RISIKO TERHADAP KINERJA KEUANGAN BANK MUAMALAT INDONESIA (Studi Kasus Pada PT. Bank Muamalat Indonesia Tbk) - Ahmad, Listian; Puspitasari, Riana (DPPM Universitas Pelita Bangsa, 2020)
This study examines the collapse of net profit and the increase in non-performing financing or “Non-Performing Financing” due to the wrong funding target carried out by Bank Muamalat Indonesia. This study aims to determine the effect of capital and operational risk on the financial performance of Bank Muamalat Indonesia. Data collection methods in this study are secondary data analysis and literature study. The subjects in this study were Bank Muamalat Indonesia with a total sample size of 30 financial reports. Methods of data analysis in this study using multiple linear regression analysis and classical assumption test. Hypothesis testing is done by using the coefficient of determination (R and R square), simultaneous significance test (F test), and partial significance test (t test). The results of the analysis show that capital has a positive regression coefficient value of 0.239 and a significance value of 0.001 (less than 0.05). While the risk has a negative regression coefficient value of -0.087 and a significance value of 0.002 (less than 0.05). Capital has a positive and significant effect on financial performance. The greater the capital a bank has, it shows that the bank is getting stronger and the bank's financial performance will increase. Risk is said to have a negative and significant effect on financial performance. The smaller the risk value faced, the bank's financial performance will increase